POTENTIAL OF ACEH ARABICA COFFEE EXTRACT (Coffea arabica L.) IN REJUVENATION OF AGING SKIN IN RAT - Safrida Safrida; Mustafa Sabri (Jurnal Kedokteran Hewan, 2017)
This study aimed to u determine the potency of Aceh Arabica coffee In rejuvenation of aging skin in rat. This study was conducted in vivousing completely randomized design (RAL), which consisted of 4 treatment groups as follows: premenopausal rats as negative control (KON),premenopausal rats with administration of distilled water as placebo (PLS), premenopausal rats with administration of ethinylestradiol 9x10-3mg/day/200 g BW (EST), and premenopausal rats with coffee extract administration of 300 mg/day/200 g BW (KOP). Each treatment groupconsisted of 5 rats. The parameters observed were skin collagen, water content/skin hydration, and skin ribonucleic acid (RNA) level. The datawere analyzed using analysis of variance (ANOVA) and Duncan test using SAS 9.13 software. The result showed the average skin collagen andRNA levels were higher in premenopausal rats with administration of coffee extract and ethinylestradiol (P0.05) than control rats. On the otherhand, average of water level in premenopausal rats with coffee extract and ethinylestradiol administration were the same as control rats. It can beconcluded that administration of Aceh Arabica coffee extract can repair skin quality, which is indicated by the increase of collagen and RNAlevel on aging skin in rat.